Power-take off design for energy harvesting in flow induced vibration systems - Sng, Chin Chye (2014)
The need to source for renewable energy is crucial for the vast advancement of technologies which taxes on the high energy consumption. Burning of finite resources such as coals is required and affects much on the global environmental pollution. The design of a Power-take off (PTO) system is conducted to study on the nonlinear characteristic applied onto the structure. Using the Vortex Induced Vibration (VIV) phenomenon, energy shall be harvested from the mechanical motion induced by it. A literature review of such phenomenon is discussed with parameters that govern the characteristic. It is experimentally studied to analyze alternatives methods to enhance on non-linearity characteristic of the structure. This will lead to the investigation on the widening of frequency of harvesting of energy using non-linearity. Different strength of nonlinear springs is explored with the usage of additional plates and different materials. Experiments are conducted with a 0.05m diameter cylinder under velocities range from 0.13 to 0.562 m/s. Comparison with other reports will be presented to show that the modified structure is enhanced. Also, experiment results proves that the high hardening stiffness configurations with the suitable material shall be used to enable energy harvesting in a large range of reduced velocities. The efficiency of the system is improved and proved that it to be able to harvest energy during low velocities where slight non linearity configurations could not.